1996
DOI: 10.1111/j.1365-2133.1996.tb06332.x
|View full text |Cite
|
Sign up to set email alerts
|

Black breast milk due to minocycline therapy

Abstract: We report the unusual case of a 29-year-old female who developed black discoloration of breast milk 3 weeks after commencing oral minocycline therapy for acne vulgaris. Histochemical analysis of the breast milk revealed the presence of pigment particles within macrophages with iron staining characteristics. We propose that the pigment may represent an iron chelate of minocycline or one of its derivatives.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 9 publications
0
12
0
Order By: Relevance
“…These findings have been reproduced in human case reports. Glandular deposition of iron-bound pigment may be responsible for several cases of black galactorrhea in women [28,29]. It is unclear if similar deposits cause discoloration of connective and cardiac valvular tissues [30].…”
Section: Are There Other Manifestations Of Minocycline Discoloration?mentioning
confidence: 99%
“…These findings have been reproduced in human case reports. Glandular deposition of iron-bound pigment may be responsible for several cases of black galactorrhea in women [28,29]. It is unclear if similar deposits cause discoloration of connective and cardiac valvular tissues [30].…”
Section: Are There Other Manifestations Of Minocycline Discoloration?mentioning
confidence: 99%
“…5,6,14 In one study of 700 adult patients, pigmentation only occurred after a minimum of eight months and with a cumulative dose exceeding 70 g. 5 The prevalence was 0.4 per cent at a dose of 100 mg/day and 4 per cent at 200 mg/day, 4 although the effect is also reported as presenting independently of both cumulative dose and time. 8,15 Benitz et al 1 initially reported minocy c l i n e -i n d u c e d soft tissue pigmentation in 1967, the same year as its introduction into clinical practice, describing an abnormal discoloration in the thyroid gland in rats, dogs and monkeys. The pigmentation is caused by polymerization of the oxidation products, 9-hydroxy and N-demethylated derivatives, to form an ironbinding melanin-like molecule.…”
Section: Pigmentationmentioning
confidence: 99%
“…Black breast milk has also been described follow i n g minocycline administration. 8,21 Although one report indicated several years of therapy, another case occurred after only three weeks. Examination of the milk revealed macrophages containing pigmented particles consistent with haemosiderin, suggesting a similar pathogenesis to cutaneous pigmentation.…”
Section: Pigmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…The pigmentation can reach the conjunctiva, buccal mucosa [64, 69], lips [70] and bone to create a dark bone pigmentation severe enough to be visible through the alveolar and palatal mucosa [71]. A breast milk discoloration was reported: the milk had turned black 3–4 weeks after beginning therapy with 150 mg daily for acne [72]. These adverse reactions are important and worrying, but fortunately they are rare; so the treatment is usually safe [73].…”
Section: General Methods Of Treatment and Side Effectsmentioning
confidence: 99%